Issues and development prospects of the passenger transport in the city of Kharkiv: sociological and geographical aspect - ОтечкоC. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
Passenger transport is a most important part of Kharkiv transport system. Each of modern modes of transport – with their own features and infrastructure – functions as a whole system, while there is a range of problems encountered in the field. Metro carries the largest number of passengers in Kharkiv, which is attributable to its advantages: it faces no traffic congestion; it operates equally efficiently in any time or season of the year. This mode faces such issues as relatively low trains’ speed, limited branching around the city. Motor vehicle takes the second place based on the transportations number. The major advantage is its mobility, and disadvantages include considerable impact on ecology, enlarged number of vehicles and enlarged congestion on city roads. Trolleybus transport is the least hazardous for the environment. The disadvantages include limited mobility, exhausted rolling stock, catenary system, and road surface. Trams occupy the last place by the number of passengers carried in Kharkiv. It has the following advantages: eco-friendly, costs cheaper in use, its technical lifespan is longer. It faces the following issues: tram lines are expensive in laying and service, need rational ways of laying, rolling stock is scarcely repaired or replaced. Having studied the public transport main modes in Kharkiv, we provide recommendations to this system optimization. Premetro is proposed as an alternative to the tram. It is separated from the traffic flow and allows for saving on the rolling stock. Among disadvantages, there is less capacity as compared to the metro, and higher construction costs compared to the tram. It is reasonable to introduce premetro on the perspective areas of metro building. We find single rail transport to be promising. It does not overload automobile roads, and congestion has no effect on it, it gathers great speed and produces little noise, its construction takes less time, it is five to ten times cheaper in building compared to the metro, and two to three times cheaper than city automobile overpasses. It has its disadvantages as well. There are higher servicing costs,passengers get locked in a train if an unplanned stop takes place. Single rail transport is perspective to unite end metro stations.